Investment and Institutional Strengthening in Garut District: The Role of Government in the Implementation of Investment Policies - Widaningsih, Widaningsih; Nurlia, Elly; Asiyah, Asiyah; Gugun, Gugun; Wawan, Wawan (Universitas Sultan Ageng Tirtayasa, 2025)
Investment is an important component in regional economic development, but its realization in Garut District is still far from the set target. This research aims to analyze the role of the government in strengthening institutions to support the implementation of investment policies in Garut District. A qualitative method is used to collect and analyze data, with in-depth interviews involving approximately 18 informants, consisting of related services, investors, and the community, supported by a documentation study. The research results show that there is a significant gap between interest in investment and its realization in Garut District, mainly due to the government’s suboptimal role in strengthening institutions related to investment. The main challenges identified include inconsistent regulations, bureaucratic obstacles, and weaknesses in coordination and communication between executing institutions. This research emphasizes the importance of strengthening the institutional framework as a prerequisite for implementing effective investment policies at the regional level. From a theoretical perspective, this research contributes to the development of concepts regarding the institutional role in the implementation of investment policies. From a practical perspective, the results of this research can provide input for the Garut District government in formulating strategies to improve coordination, data availability, and the simplification of investment management procedures, thereby increasing investment realization and fostering regional economic growth.